The relationship between inflation and money supply towards Real Estate Investment Trusts (REITs) in Malaysia / Siti Nurulaine Md Iskandar Dzulkarnain - Md Iskandar Dzulkarnain, Siti Nurulaine (2016)
In this paper the researcher wants to investigate the relationship between the inflation and money supply towards the Real Estate Investment Trusts (REITs). From the previous research, money supply and inflation will be in different journal but still discuss on the effect towards REITs Return. The dividend yield use to measure REITs Return. The Consumer Price Index (CPI) to show the Inflation and Money Supply use M2 that is more stable than M1 and also M3. The quantitative data required for this research were extracted from the Datastream of the AXIS REITs Company with the period from January 2009 to December 2014. The method use is by Regression Analysis that includes the descriptive analysis, stationary test, correlation analysis, normality test and Heteroskedasticity.